2011
DOI: 10.1038/emboj.2011.16
|View full text |Cite
|
Sign up to set email alerts
|

Subunit-selective N-terminal domain associations organize the formation of AMPA receptor heteromers

Abstract: The assembly of AMPA-type glutamate receptors (AMPARs) into distinct ion channel tetramers ultimately governs the nature of information transfer at excitatory synapses. How cells regulate the formation of diverse homo-and heteromeric AMPARs is unknown. Using a sensitive biophysical approach, we show that the extracellular, membrane-distal AMPAR N-terminal domains (NTDs) orchestrate selective routes of heteromeric assembly via a surprisingly wide spectrum of subunit-specific association affinities. Heteromeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
185
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(209 citation statements)
references
References 81 publications
23
185
1
Order By: Relevance
“…priority, supporting the notion that the ATDs are critical for the first step of heterodimerization (11,31,33).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…priority, supporting the notion that the ATDs are critical for the first step of heterodimerization (11,31,33).…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies demonstrated that heterodimers could be formed both in isolated ATDs of GluA2 and GluA3 (39,40) and in kainate receptors (20,41). The velocity sedimentation study of isolated ATDs shows that the heterodimer of GluA1/A2 ATDs has the smallest dissociation constant (K d ); thus, the heterodimers are preferred (31). In our study, ATDs form heterodimers in the full-length GluA1/A2.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, there is considerable flexibility in the NTD dimer interface that allows the formation of GluA2-lacking AMPARs when appropriate to the relevant physiological and pathological conditions. 75 . Most assembled AMPAR tetramers contain GluA2 9 and this is strongly regulated by Q/R editing of the GluA2 subunit.…”
Section: Rna Editing Ampar Assembly and Er Exitmentioning
confidence: 99%
“…Previous studies have identified structural elements that contribute to the assembly of AMPARs in almost every domain (5,11,12). The ATD of AMPARs forms dimers in solution and drive the initial dimerization process (13)(14)(15). Alternative splicing in the LBD (flip/flop) influences subunit composition of AMPAR heteromers, potentially by affecting the tetramerization process (16).…”
mentioning
confidence: 99%